2014
DOI: 10.1590/s1517-83822014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by Staphylococcus aureus from food contact surfaces in a meat-based broth and sensitivity to sanitizers

Abstract: This study assessed the capacity of adhesion, the detachment kinetic and the biofilm formation by Staphylococcus aureus isolated from food services on stainless steel and polypropylene surfaces (2 × 2 cm) when cultivated in a meat-based broth at 28 and 7 °C. It was also to study the efficacy of the sanitizers sodium hypochlorite (250 mg/L) and peracetic acid (30 mg/L) in inactivating the bacterial cells in the preformed biofilm. S. aureus strains adhered in high numbers regardless the assayed surface kind and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 34 publications
5
49
0
5
Order By: Relevance
“…Moreover, the ability of S. aureus isolated from industrial surfaces to form biofilm depends on the environmental conditions. The hygienic condition of food handlers is also associated with the propagation of S. aureus biofilm producer (Gutiérrez et al 2012, Souza et al 2014, Di Ciccio et al 2015. Several authors have reported E. faecalis strains isolated from food samples with ability to form biofilms (Medeiros et al 2014, Jahan and Holley 2014, Fernandes et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ability of S. aureus isolated from industrial surfaces to form biofilm depends on the environmental conditions. The hygienic condition of food handlers is also associated with the propagation of S. aureus biofilm producer (Gutiérrez et al 2012, Souza et al 2014, Di Ciccio et al 2015. Several authors have reported E. faecalis strains isolated from food samples with ability to form biofilms (Medeiros et al 2014, Jahan and Holley 2014, Fernandes et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborando esta hipótesis, en el cultivo de células en caldo de soja tríptico a temperaturas inferiores a las óptimas (20, 25 y 30°C), Rode et al (21) encontraron la mayor capacidad de fijación de S. aureus en poliestireno. De Souza et al (22) observaron que las cepas de S. aureus se adhirieron en grandes cantidades independientemente del tipo de superficie evaluada y de la temperatura de incubación (7 o 28ºC). Por lo tanto, nuestros resultados sugieren la necesidad de mejores procesos de inactivación o eliminación de agentes contaminantes en las superficies de suppression of motility, changes in morphology, and fertilizing capacity.…”
Section: Discussionunclassified
“…The assayed strains revealed high capacities to adhere and form biofilms on polypropylene and stainless steel surfaces under different growth conditions, and the cells in biofilm matrixes were resistant to total removal when exposed to the sanitizers such as sodium hypochlorite and peracetic acid (Souza et al, 2014;Jerônimo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is assumed that cell aggregates or biofilm formation by S. aureus can be a potential risk for food cross-contamination (Souza et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation